OS 16-06 RISK FACTORS FOR SERIOUS FALL INJURIES FOLLOWING INITIATION OF ANTIHYPERTENSIVE MEDICATION. (September 2016) - Reynolds, Kristi; Shimbo, Daichi; Bowling, C. Barrett; Deng, Luqin; Bress, Adam; Sim, John; Muntner, Paul
Abstract : Objective: To identify risk factors for serious fall injuries following initiation of antihypertensive medication among older adults. Design and Method: We conducted a retrospective cohort study using a 5% random sample of people with Medicare health insurance, a government program for older US adults. The analysis was restricted to patients with a diagnosis of hypertension who initiated antihypertensive medication between 2007 and 2011. Initiation was defined by the first antihypertensive medication fill in this time period preceded by 365 days with no antihypertensive medication fills. Fall risk factors were determined from claims in the 365 days before antihypertensive medication initiation. Serious fall injuries were defined based on emergency department and inpatient claims with an injury code for nonpathological fractures, brain injury, or dislocation of the hip, knee, shoulder, or jaw, along with a fall-related code; or along with the requirement that there was no motor vehicle accident code in the absence of a fall-related code. Results: The mean (SD) age of patients who initiated antihypertensive medication (n = 65, 179) was 76.3 (7.6), 60.5% were women, and 8.8% were black. There were 2, 174 serious fall injuries during the year following medication initiation. The incidence rate per 1, 000 person-years of serious fall injuries was 45.9 (95% CI, 44.2 - 47.6). Independent risk factors for serious fall injuries included older age, female sex, white race, history of stroke, syncope, osteoporosis, depression or dementia, use of >10 medications, Charlson comorbidity index >0, and serious fall injuries in the year prior to antihypertensive medication initiation (Table). Conclusions: These results suggest that selected demographic and clinical characteristics identify patients at high risk for serious fall injuries following antihypertensive medication initiation. Conducting fall risk factor assessment in older adults initiating antihypertensive medication may be a strategy to improve the recognition of those at risk for serious fall injuries.